(untitled) (Communications in Computational Physics, 2010)
In this paper, we propose a lattice Boltzmann (LB) method coupled with a direct-forcing fictitious domain (DF/FD) method for the simulation of particle suspensions. This method combines the good features of the LB and the DF/FD methods by using two unrelated meshes, namely, an Eulerian mesh for the flow domain and a Lagrangian mesh for the solid domain, which avoids the re-meshing procedure and does not need to calculate the hydrodynamic forces at each time step. The non-slip boundary condition is enforced by introducing a forcing term into the lattice Boltzmann equation, which preserves all remarkable advantages of the LBM in simulating fluid flows. The present LB-DF/FD method has been validated by comparing its results with analytical results and previous numerical results for a single circular particle and two circular particles settling under gravity. The interaction between particle and wall, the process of drafting-kissing-tumbling (DKT) of two settling particles will be demonstrated. As a manifestation of the efficiency of the present method, the settling of a large number (128) of circular particles is simulated in an enclosure.